Pull-Out and Tensile Strength Properties of Two Selected Tropical Trees - Osman, Normaniza; Abdullah, C.H.; Abdullah, M.N. (Penerbit Universiti Kebangsaan Malaysia, 2011)
A bioengineering technique is gradually being used as an alternative for slope stabilisation design. The effect of vegetation on soil strength, particularly in terms of root reinforcement aspects has therefore become a major interest. However, there is a lack of documentation on the root mechanical properties available especially in Malaysia. In this study, both pull-out and tensile strength of two tropical trees namely Leucaena leucocephala and Acacia mangium were investigated on different stem sizes. L. leucocephala performs the higher pullout strength than A. mangium. The results also show that pullout resistance is much affected by the root than the shoot profiles. In terms of tensile strength, the tensile strength decreases with increasing root diameter, implying the finer root diameter contribute to the higher tensile strength. In both parameters, L. leucocephala exhibits the highest value. The study suggests that L. leucocephala has an added value as a good potential slope plant for slope stabilization work as it exhibits outstanding root mechanical properties. Interestingly, the results also showed that the pullout force was much affected by the tensile strength. It can be concluded that some root and shoot properties do have a great impact on root mechanical properties such as tensile and pullout strengths.